Principles of group accounting under IFRS - Krimpmann, Andreas, 1963- (Chichester, West Sussex, UK : Wiley, Inc., 2015)
List of figures xiv List of tables xvii Preface xix Introduction to the book xx A The case study 1 1. About the group 1 2. Allocation of examples 1 B Legal requirements for consolidated financial statements 4 1. IFRS standards 5 2. Exemptions 18 3. Local accounting standards 19 4. Taxation 20 5. Definitions 21 C Definition of groups 22 1. The control concept 23 2. Joint control 28 3. Loss of control 31 4. Group compositions 33 5. Special cases 34 D Preparation of consolidated financial statements and annual reports 37 1. Lifecycle of subsidiaries 38 2. Structures 39 3. T.
6.6. Shares of the parent company6.7. Non-material subsidiaries; F Subsequent consolidation; 1. Basics; 1.1. Preparation mechanics; 1.2. Tasks & timing; 2. Subsidiary preparation; 3. Equity consolidation; 3.1. Consolidation requirements; 3.2. Consolidation techniques; 3.3. Special cases; 4. Debt consolidation; 4.1. Intercompany relationships; 4.2. Consolidation techniques; 4.3. Differences; 4.4. Preventative activities; 4.4.1. Organizational aspects; 4.4.2. Simple settlement; 4.4.3. Netting; 5. Consolidation of income and expenses; 5.1. Intercompany relationships.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Accounting -- Standards; Financial statements, Consolidated; BUSINESS & ECONOMICS / Accounting / Financial; Accounting -- Standards; Financial statements, Consolidated; Accounting -- Standards; Accounting; Financial statements, Consolidated; Electronic books; Electronic books